Cellular Landscapes of Nondiseased Human Cardiac Valves From End-Stage Heart Failure–Explanted Heart - Shu, Songren; Fu, Mengxia; Chen, Xiao; Zhang, Ningning; Zhao, Ruojin; Chang, Yuan; Cui, Hao; Liu, Zirui; Wang, Xiaohu; Hua, Xiumeng; Li, Yuan; Wang, Xin; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2022)
Exploring the mechanisms of valvular heart disease at the cellular level may be useful to identify new therapeutic targets; however, the comprehensive cellular landscape of nondiseased human cardiac valve leaflets remains unclear. The cellular landscapes of nondiseased human cardiac valve leaflets (5 aortic valves, 5 pulmonary valves, 5 tricuspid valves, and 3 mitral valves) from end-stage heart failure patients undergoing heart transplantation were explored using single-cell RNA sequencing. Bioinformatics was used to identify the cell types, describe the cell functions, and investigate cellular developmental trajectories and interactions. Differences among the 4 types of cardiac valves at the cellular level were summarized. Pathological staining was performed to validate the key findings of single-cell RNA sequencing. An integrative analysis of our single-cell data and published genome-wide association study-based and bulk RNA sequencing-based data provided insights into the cell-specific contributions to calcific aortic valve diseases. Six cell types were identified among 128 412 cells from nondiseased human cardiac valve leaflets. Valvular interstitial cells were the largest population, followed by myeloid cells, lymphocytes, valvular endothelial cells, mast cells, and myofibroblasts. The 4 types of cardiac valve had distinct cellular compositions. The intercellular communication analysis revealed that valvular interstitial cells were at the center of the communication network. The integrative analysis of our single-cell RNA sequencing data revealed key cellular subpopulations involved in the pathogenesis of calcific aortic valve diseases. The cellular landscape differed among the 4 types of nondiseased cardiac valve, which might explain their differences in susceptibility to pathological remodeling and valvular heart disease.